2017
DOI: 10.22146/ajche.49892
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Biosorption of Cd(II) and Cu(II) in Single and Binary Metal Systems by Water Hyacinth (Eichhornia crassipes) using Aspen Adsorption

Abstract: Biosorption is becoming an attractive alternative for the removal of heavy metal from contaminated wastewaters since it offers low capital and operating costs. It has a great potential on heavy metal decontamination and the possibility of metal recovery. The study evaluated the performance of water hyacinth (Eichhornia crassipes) in a fixed bed column on sequestering heavy metals present in wastewaters. Column breakthrough curves at varying parameters were evaluated. The study used Aspen Adsorption® to simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…The aquatic plant, E. crassipes, grows in wetlands and is usually contaminated with organic matter, which tends to its rapid expansion in the surface where a layer is created that does not allow oxygen access to the interior of the water; therefore, they cease to exist microorganisms vital to the ecosystem. (Martínez et al 2013;Saraswat and Rai 2010;Feng et al 2017;Liu et al 2018;Mohammed et al 2018;Adornado et al 2017;Rani et al 2017;Mahunon et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The aquatic plant, E. crassipes, grows in wetlands and is usually contaminated with organic matter, which tends to its rapid expansion in the surface where a layer is created that does not allow oxygen access to the interior of the water; therefore, they cease to exist microorganisms vital to the ecosystem. (Martínez et al 2013;Saraswat and Rai 2010;Feng et al 2017;Liu et al 2018;Mohammed et al 2018;Adornado et al 2017;Rani et al 2017;Mahunon et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Analyzing data from Table 7, it was noticed that q0 gradually increased with the increase in height and mass of NaY zeolite, as expected. The authors Nieva et al (2019) and Adornado et al (2016) found similar behaviours with the variation of Hb, for the estimated breakthrough curves for ion exchange of metallic ions with biomass, using the MTSF model of Adsim. A column with lower height implies a lower capacity of the bed to remove metal ions from the solution and, therefore, resulting in a faster rupture and saturation time, as shown in Table 7, where the shortest saturation time (t = 282 min) was detected for the lowest height (Hb = 0.012 m).…”
Section: Simulation Of Breakthrough Curvesmentioning
confidence: 58%
“…The Adsim model was used in recent researches, such as simulation of the ion exchange of Cu2+ in aqueous solution with the biomass Cucumis melo VAR. cantalupensis, (Nieva et al, 2018), Cu(II) and Cr(III) on charcoal (Zhang et al, 2019) and Cd (II) and Cu (II) in simple and binary metallic systems with the biomass Eichhornia crassipes (Adornado et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The treatment with iron (Fe), optimized the efficiencies of Cr (VI), showing more treatment time and treating about 25% more water. The experiment of [37] had an efficiency of 73% of Cr (VI) with the (EC); in [25], this biomass also had an efficiency of 85% for Cr (VI), and in [30] the efficiency of Cd (II) was 85% (see Table 1). Algae 300 85 Cu (II) [41] Almond shell 100 95 Cr (VI) [42] Biomass + Fe 100 96 Cr (VI) [28] Bacillus + Biochar 100 95 Cr (VI) [42] Biochar + Fe 100 98 Cr (VI)…”
Section: Experimental Processmentioning
confidence: 99%
“…In [28][29][30], the authors experimented on batch, determining the design parameters and scaling the results by developing fixed columns for the treatment of heavy metals with biochar. The mass balances were used to determine the amount of pollutant load that must be treated, thus achieving the discharge aims [31].…”
Section: Introductionmentioning
confidence: 99%